Differences in attachment dimensions and reflective functioning between traumatized juvenile offenders and maltreated non-delinquent adolescents from care services - Protic, Sonja; Wittmann, Lutz; Taubner, Svenja; Dimitrijević, Aleksandar (Child abuse & neglect, 2020)
Background - Adverse childhood experiences, especially maltreatment, are regarded as significant risk factors for the development of antisocial behavior in adolescence. However, possible correlates are still to be investigated after considering the history of criminal records and the experience of institutionalization. - Objective - In this study, differences in attachment anxiety and avoidance, and reflective functioning (RF) between traumatized incarcerated juvenile offenders and non-delinquent adolescents institutionalized in child services because of domestic violence were examined. - Participants, setting and method - Forty-two juvenile offenders (Nfemale = 19) and 43 inmates of institutions for adolescents without parental care (Nfemale = 20) with the history of trauma filled in the childhood trauma and attachment dimensions questionnaires, and were scored on the Reflective Functioning Scale. Groups were matched on age and education. - Results - Results indicate that both groups reported equally high levels of attachment anxiety and avoidance. Male juvenile offenders had lower scores on reflective functioning than both female convicted minors (B = 1.06; Odds Ratio = 2.88; Nagelkerkes R2 = 45) and non-delinquent adolescents of both genders (B = −.65; Odds Ratio = .52; Nagelkerkes R2 = 42). In comparison to non-convicted males, male offenders also had higher scores on the control scale of idealization (B = .35; Odds Ratio = 1.42; Nagelkerkes R2 = 42). No differences between females with and without a history of crimes were found. - Conclusions - Results indicate a need for building RF in both traumatized samples, especially in male delinquents, and encourage further research in females.